ON THE PROSPECTS AND RISKS OF INTERSTATE COOPERATION IN COMBATING CRIME WITH THE USE OF NEW TECHNOLOGIES UNDER THE AUSPICES OF THE UNITED NATIONS - SKIRDA Maksim Vladimirovich (Правовое государство: теория и практика, 2025)
The measures taken by the international community to combat crime are being developed and implemented in the context of new challenges associated with the process of globalization. In the article, the author analyzes international legal acts affecting the use of artificial intelligence, digital technologies in the field of crime prevention and criminal justice. The purpose of the study is to consider the debatable issues of the validity of the use of artificial intelligence and digital technologies in the fight against modern crime, to determine the prospects for the legal regulation of the use of artificial intelligence in international criminal law. Methods: the dialectical method of cognition, synthesis, deduction and induction, formal-legal, historical-legal and the method of comparative law. Results: the study reveals that modern digital technologies, when used responsibly, contribute to the implementation of the rule of law. At the same time, new technologies can pose a threat to the right to privacy, undermine the foundations of state security, and increase inequality in society. The author highlights the shortcomings of the uncontrolled spread of new technologies. The author concludes that national criminal justice systems must be prepared to withstand the negative impact of the uncontrolled spread of advanced technologies. At the normative level, universal, binding standards are needed to address the growing problems associated with the criminal misuse of information and communication technologies. In the future, it seems expedient to adopt a universal international law instrument on the suppression and prevention of the criminal use of information and communication technologies.